The Rust programming language - Klabnik, Steve; Nichols, Carol, 1983- (No Starch Press, Inc., 2023)
"The Rust Programming Language, 2nd Edition is the official guide to Rust 2021: an open source systems programming language that will help you write faster, more reliable software. Rust provides control of low-level details along with high-level ergonomics, allowing you to improve productivity and eliminate the hassle traditionally associated with low-level languages."--Publisher's description.